Functional dentition, dietary intake and nutritional status in Thai older adults. (26th April 2019) - Gaewkhiew, Piyada; Sabbah, Wael; Bernabé, Eduardo
Abstract: Objectives: To explore the relationship between functional dentition and nutritional status among Thai older adults, and the role of nutrient intake in this association. Background: Evidence on the interplay between tooth retention, diet and nutritional status is still inconclusive, with most evidence coming from Western countries. Methods: Seven hundred and eighty‐eight Thai adults, aged 60+ years, living in Phetchaburi Province, Thailand, participated in this cross‐sectional study. Data were collected through questionnaires, body measurements and dental examinations. Being underweight (Body Mass Index < 18.5) and overweight/obese (BMI > 25) were the two outcome measures. Functional dentition was defined as having 10+ functional tooth units. The association of functional dentition with each outcome was assessed in regression models adjusted for sociodemographic factors, behaviours, chronic conditions and total energy intake. The role of various nutrients in explaining the above associations was quantified via the per cent attenuation in the coefficient for functional dentition. Results: Functional dentition was associated with being underweight but not with being overweight/obese. After adjustments, participants with functional dentition were 61% (prevalence ratio: 0.39, 95% CI: 0.16, 0.95) less likely to be underweight than those with neither functional dentition nor dentures. In addition, participants with functional dentition had significantly greater intake of dietary fibre and thiamine (Vitamin B1 ) than those with neither functional dentition nor dentures. The two nutrients explained a small part of the association between functional dentition and being underweight. Conclusion: Having a functional dentition was negatively associated with being underweight. The consumption of dietary fibre and thiamine explained a small part of this association.